Fundamental frequencies in the Schwarzschild Spacetime (Physical Sciences and Technology, 2018)
We consider the Keplerian, radial and vertical fundamental frequencies in the Schwarzschild spacetime tostudy the so-called kilohertz quasi-periodic oscillations from low-mass X-ray binary systems. We show that,within the Relativistic Precession Model, the interpretation of observed kilohertz quasi-periodic oscillations interms of the fundamental frequencies of test particles in the Schwarzschild spacetime, allows one to infer thetotal mass M of the central object, the internal Rin and external Rex radii of accretion disks, and innermost stablecircular orbits rISCO for test particles in a low-mass X-ray binary system. By constructing the relation betweenthe upper and lower frequencies and exploiting the quasi-periodic oscillation data of the Z and Atoll sources weperform the nonlinear model fit procedure and estimate the mass of the central object. Knowing the value of themass we calculate the internal Rin and external Rex radii of accretion disks and show that they are larger thanrISCO, what was expected.